2018
DOI: 10.1021/acsnano.8b03010
|View full text |Cite|
|
Sign up to set email alerts
|

Blinking Suppression in Highly Excited CdSe/ZnS Quantum Dots by Electron Transfer under Large Positive Gibbs (Free) Energy Change

Abstract: Semiconductor quantum dots with stable photoluminescence are necessary for next generation optoelectronic and photovoltaic devices. Photoluminescence intensity fluctuations of cadmium and lead chalcogenide quantum dots have been extensively investigated since the first observation of blinking in CdSe nanocrystals in 1996. In a quantum dot, blinking originates from stochastic photocharging, nonradiative Auger recombination, and delayed neutralization. So far, blinking is suppressed by defect passivation, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…Charge separation dynamics with the use of various electron acceptors has been reported in many papers. [5][6][7][8][9][10][11][12][13][14][15][16][17] For example Banin et al reported that hybrid nanostructures of Au-tipped CdS nanorods with a larger Au size exhibited a higher probability for charge separation of multiple excitons formed in the CdS nanocrystals, improving the photocatalytic activity for H 2 generation. 15 The rate of photoinduced electron transfer from CdSe NCs to methyl viologen (MV 2+ ) was shown to be dependent on the particle morphology: plate-like CdSe NCs exhibited a slower rate than that of spherical or rod-shaped CdSe NCs due to the weak electronic coupling along the short and long axes in the lateral dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Charge separation dynamics with the use of various electron acceptors has been reported in many papers. [5][6][7][8][9][10][11][12][13][14][15][16][17] For example Banin et al reported that hybrid nanostructures of Au-tipped CdS nanorods with a larger Au size exhibited a higher probability for charge separation of multiple excitons formed in the CdS nanocrystals, improving the photocatalytic activity for H 2 generation. 15 The rate of photoinduced electron transfer from CdSe NCs to methyl viologen (MV 2+ ) was shown to be dependent on the particle morphology: plate-like CdSe NCs exhibited a slower rate than that of spherical or rod-shaped CdSe NCs due to the weak electronic coupling along the short and long axes in the lateral dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of processes such as intraband relaxation, multiple exciton generation, nonradiative Auger recombination, and emission from biexcitons ,,,− increase with decreasing size in the quantum-confined regime . In strongly confined spherical QDs, sub-100 ps Auger-type annihilation of biexcitons and recombination of trions gives both of these species a much lower PL quantum yield than single excitons in the same material, such that emission from these species is generally only observable when their radiative rates are enhanced ( e.g ., by an external field) or when the Auger rate is slowed at low temperature. …”
Section: Multiparticle States and Charged Nanocrystalsmentioning
confidence: 99%
“…One of the downsides of QDs is the intermittent nature of their PL (blinking) that occurs when one or both components of an exciton (electron and hole) hit the surface of the particle, which leads to the appearance of a charge on the particle and quenching of the PL as a result of nonradiative recombination [ 49 ]. In order to overcome this drawback, several methods have been designed that provide complete or partial blinking suppression [ 50 , 51 ].…”
Section: Quantum Dotsmentioning
confidence: 99%